VO(2)FITTING: A Free and Open-Source Software for Modelling Oxygen Uptake Kinetics in Swimming and other Exercise Modalities - Zacca, Rodrigo (Sports (Basel), 2019)
The assessment of oxygen uptake (VO(2)) kinetics is a valuable non-invasive way to evaluate cardiorespiratory and metabolic response to exercise. The aim of the study was to develop, describe and evaluate an online VO(2) fitting tool (VO(2)FITTING) for dynamically editing, processing, filtering and modelling VO(2) responses to exercise. VO(2)FITTING was developed in Shiny, a web application framework for R language. Validation VO(2) datasets with both noisy and non-noisy data were developed and applied to widely-used models (n = 7) for describing different intensity transitions to verify concurrent validity. Subsequently, we then conducted an experiment with age-group swimmers as an example, illustrating how VO(2)FITTING can be used to model VO(2) kinetics. Perfect fits were observed, and parameter estimates perfectly matched the known inputted values for all available models (standard error = 0; p < 0.001). The VO(2)FITTING is a valid, free and open-source software for characterizing VO(2) kinetics in exercise, which was developed to help the research and performance analysis communities.